The relationship between swimming performance and time parameters of the start and turn - Grznár, L.; Jurák, D.; Labudová, J. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2019)
The start and the turn are factors that influence performance in different swimming disciplines. The aim of this study was to find out the relationship of selected time parameters of the start and the turn with sport performance of 100 m and 1 500 m freestyle finalists in the Olympic Games 2016. Monitored parameters of the start were the start reaction, time under water after the start, and time at a distance of 15 m after the start. The monitored parameters of the turn were the time of 5 m before the turn, the duration of the turn, the time under water after the turn, and time reached at a distance of 15 m after the turn. There was any significant correlation of the resulting time to 1 500 m and the observed start indicators. The significant correlation of the resulting time to 1 500 m and the observed turn indicators was time 5 m before the turn r = 0.952 (p = 0.000); the duration of the turn r = 0.830 (p = 0.011); time at a distance of 15 m after the turn r = 0.886 (p = 0.003). The significant correlation of the resulting time to 100 m and the observed start indicators was time under water after the start r = -0.714 (p = 0.047). The significant correlation of the resulting time to 100 m and the observed turn indicators was the duration of the turn was r = 0.905 (p = 0.002). The results point out the existing relations between 100 m freestyle and time under water after start and duration of the turn. And for 1 500 m existing relations with time 5 m before the turn, the duration of the turn and time at a distance of 15 m after the turn. Therefore, our recommendations for sports practice include development of speed, power and coordination skills with technical execution of the start and the turn into regular swimming training.